A comparative assessment of approaches and outcomes for seagrass revegetation in Shark Bay and Florida Bay - Statton, J.; Dixon, Kingsley; Hovey, R.; Kendrick, G. (2012)
Here, we review the literature to evaluate seagrass revegetation projects focussed on Posidonia australis and Amphibolis antarctica, the main affected species in Shark Bay in the World Heritage Area in Western Australia, together with projects from Florida Bay, an analogous system with a long history of seagrass revegetation. We assessed the effectiveness of anchoring planting units, plant-unit density and size on planting-unit survival. We found no positive trends in our assessment, suggesting that there is no discrete technique, approach or technology that could be used with confidence to deliver cost-effective, scalable revegetation. Of concern was that revegetation success was evaluated over comparatively short time frames (1–3 years), driven by the strict time frames or deadlines of governing grant funding and commercial activities, leading to concerns that long-term revegetation outcomes may be difficult to assess with confidence. Several factors influenced revegetation outcomes which were grouped into three ‘filter’ categories; abiotic, biotic and socioeconomic. We recommend that future revegetation programs involving seagrass have greater emphasis on understanding how these filters act independently or collectively to drive successful revegetation as well as developing cost-effective, proven and scalable technology supported by longer-term monitoring to ensure revegetation programs do achieve the desired ecological outcomes.